Our Changing Rural Society: Perspectives and Trends by James H. Copp; Agricultural Sociology, a Study of the Sociological Aspects of American Farm Life by Walter L. Slocum; Rural Life in an Urbanized Society by Lee Taylor, Arthur Jones, Jr.; Yearbook, 1963: A Place to Live by United State Department of Agriculture; Yearbook, 1964: The Farmer's World by United States Department of Agriculture - Zimmerman, Carle C. (Revista Mexicana de Sociología, 2020)
No disponible.